Kemandirian Anak Usia 5-6 Tahun di Lembaga PAUD pada Budaya Suku Dayak Kanayant - Lailatul Aisi Alhq; Hapidin Hapidin; Karnadi Karnadi (Universitas Mathla'ul Anwar Banten, 2020)
INDEPENDENCE OF CHILDREN AGED 5-6 YEARS AT INSTITUTION OF EARLY CHILDHOOD EDUCATION IN THE DAYAK KANAYANT CULTURE. This study aims to get an overview of empirical data information on the Independence of Children 5-6 Years in Early Childhood Education Institutions in the Dayak Kanayant Culture in Nanga Kelampai Village, Tumbang Titi District, Ketapang Regency, West Kalimantan Province. This research is a qualitative research with ethnographic research. Data analysis is Spradley. The data of this study were obtained from observations, interviews and documentation. The findings of the study indicate that the independence of children aged 5-6 years in early childhood education institutions in Kanayant Dayak tribal culture is shaped by the roles and attitudes of parents and teachers and the role of the environment. The conclusion of the research shows that independent children are not formed by themselves. Parents need to equip children from an early age to be able to do their own activities without having to rely on parents.